A Few Preliminary Comments On The Transformations Of Czech Ballad In The Years 1860 - 1918 - Dalibor Tureček (Slovenska Literatura, 2012)
The goal of the article is to draw the basic outline of the transformations of the ballad as a genre in Czech literature in the second half of the 19th century. The material is the book editions of poetry from the year 1850 to the beginning of the World War I. The method is the synoptic-pulsating approach to a literary work of art as a dynamic process within which various discourse tendencies are configured and modified. The result is a preliminary model of Czech ballad transformation in that particular period of time: the genre happened to be in the magnetic field of Romanticism represented mainly by Erben´s Kytice (Bouquet). A number of modifications occurred in the course of time, Romanticism´s genre rules became gradually more and more relaxed, especially those related to the role of plot and dynamic motifs; one of the tendencies even inclined to parody of the traditional Romantic principles of the ballad (Mašek, Hašek). At the same time the ballad was penetrated by essential features of other literary discourses such as Parnasism (Hálek, Vrchlický), Naturalism (Sládek, Šimáček) or Decadence (Jan z Wojkowicz, Lešehrad). The transformations did not take place in a linear way, within an imaginary causal „evolution“, where individual stages would „overcome“ the previous ones, but they overlapped in synoptic dynamics. The main contribution lies in the actual proof of the thesis about the nonlinear, synoptic character of transformations of a key literary genre in the 19th century, which helped establish Romanticism and has always been so attractive for readers it has stayed vital in spite of the discourse transformations.